Unveiling the therapeutic potential of cabozantinib-loaded poly D,L-lactic-co-glycolic acid and polysarcosine nanoparticles in inducing apoptosis and cytotoxicity in human HepG2 hepatocellular carcinoma cell lines and in vivo anti-tumor activity in SCID female mice - Bhattacharya, Sankha; Parihar, Vipan Kumar; Prajapati, Bhupendra G. (Frontiers in Oncology, 2023)
The study aimed to develop a nano-based drug delivery system for the treatment of hepatocellular carcinoma (HCC), a type of liver cancer that accounts for 90% of all liver malignancies. The study focused on the use of cabozantinib (CNB), a potent multikinase inhibitor that targets the VEGF receptor 2, as the chemotherapeutic drug. We developed CNB-loaded nanoparticles made from Poly D, L-lactic-co-glycolic acid, and Polysarcosine (CNB-PLGA-PSar-NPs) for use in human HepG2 cell lines.The various techniques, such as photon correlation spectroscopy, scanning electron microscopy, and transmission electron microscopy were used, to determine the formulation's particle size, zeta potential, and morphology. SYBR Green/ROX qPCR Master Mix and RT-PCR equipment used to measure liver cancer cell line and tissue mRNA expression and MTT assay to test HepG2 cell cytotoxicity. Cell cycle arrest analysis, annexin V assay, and ZE5 Cell Analyzer apoptosis assay were also performed.The results of the study showed that the particle diameters were 192.0±3.67 nm with 0.128 PDI and -24.18±3.34 mV zeta potential. The antiproliferative and proapoptotic effects of CNB-PLGA-PSar-NPs were evaluated using MTT and flow cytometry (FCM). The IC50 value of CNB-PLGA-PSar-NPs was 45.67 µg/mL, 34.73 µg/mL, and 21.56 µg/mL for 24, 48, and 72 h, respectively. The study also found that 11.20% and 36.77% of CNB-PLGA-PSar-NPs-treated cells were apoptotic at 60 µg/mL and 80 µg/mL, respectively, suggesting that the nanoparticles were effective in inducing apoptosis in the cancer cells. It can also conclude that, CNB-PLGA-PSar-NPs inhibit human HepG2 hepatocellular carcinoma cells and kill them by upregulating the tumour suppressor genes MT1F, MT1X, and downregulating MTTP, APOA4. Further in vivo antitumor activity was well reported in SCID female mice. Overall, this study suggests that the CNB-PLGA-PSar-NPs are a promising drug delivery system for the treatment of HCC, and further research is needed to investigate their potential as a clinical treatment.